2003
DOI: 10.1212/01.wnl.0000055086.35806.2d
|View full text |Cite|
|
Sign up to set email alerts
|

Practice parameter: Temporal lobe and localized neocortical resections for epilepsy

Abstract: Abstract-Objectives/Methods: To examine evidence for effectiveness of anteromesial temporal lobe and localized neocortical resections for disabling complex partial seizures by systematic review and analysis of the literature since 1990. Results: One intention-to-treat Class I randomized, controlled trial of surgery for mesial temporal lobe epilepsy found that 58% of patients randomized to be evaluated for surgical therapy (64% of those who received surgery) were free of disabling seizures and 10 to 15% were un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
296
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 794 publications
(307 citation statements)
references
References 61 publications
6
296
1
4
Order By: Relevance
“…After a randomized trial of surgery for temporal lobe epilepsy (TLE) 2 reported 64% seizure freedom, surgery was recommended as the treatment of choice for drug‐resistant TLE 3. A subsequent trial of surgery for drug‐resistant TLE of <2 years reported 85% seizure freedom, and improved quality of life and socialization 4…”
mentioning
confidence: 99%
“…After a randomized trial of surgery for temporal lobe epilepsy (TLE) 2 reported 64% seizure freedom, surgery was recommended as the treatment of choice for drug‐resistant TLE 3. A subsequent trial of surgery for drug‐resistant TLE of <2 years reported 85% seizure freedom, and improved quality of life and socialization 4…”
mentioning
confidence: 99%
“…This question is important since the treatment outcomes of TLE are variable and not completely predictable based on clinical data (Engel et al., 2003; Spencer et al., 2005); indicating that there are different TLE phenotypes that remain unidentified, but could be discerned based on imaging, if the type and the location of regular TLE abnormalities were better understood. In this study, we tested the hypothesis that microstructural abnormalities are present within a common pattern in most subjects with TLE.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Surgery is an option for some patients. Although anterior temporal lobectomy in persons with mesial temporal sclerosis can achieve a 1-to 2-year remission in Յ85% of cases, 4 resection of a well-defined neocortical lesion achieves 1-year seizure remission in only 56%. In addition to the typical risks associated with a craniotomy and general anesthesia, complications of surgery may include memory, language, visual, sensory, or motor deficits.…”
Section: Introductionmentioning
confidence: 99%